2022
DOI: 10.3350/cmh.2021.0294
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus radiofrequency ablation in patients with Child- Pugh class-A/single small (≤3 cm) hepatocellular carcinoma

Abstract: Background/Aims: We compared the post-treatment overall survival (OS) and recurrence-free survival (RFS) between patients with Child-Turcotte-Pugh (CTP) class-A and single small (≤3 cm) hepatocellular carcinoma (HCC) treated by surgical resection (SR) and radiofrequency ablation (RFA).Methods: We retrospectively analyzed 391 HCC patients with CTP class-A who underwent SR (n=232) or RFA (n=159) as first-line therapy for single small (≤3 cm) HCC. Survival was compared according to the tumor size (≤2 cm/2–3 cm) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…In recent years, regional therapies, including TACE (with or without chemotherapeutic) and RFA, have become key components of hepatocellular carcinoma treatment. Previous studies have shown no significant difference between RFA and LR regarding OS for single tumors smaller than 3 cm ( 10 12 ); however, LR may still result in better outcomes than RFA when it comes to RFS ( 39 ). Rapid advances in radiofrequency ablation equipment, improved electrodes, and the widespread use of high-resolution intraoperative ultrasound have increased the advantages of RFA.…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, regional therapies, including TACE (with or without chemotherapeutic) and RFA, have become key components of hepatocellular carcinoma treatment. Previous studies have shown no significant difference between RFA and LR regarding OS for single tumors smaller than 3 cm ( 10 12 ); however, LR may still result in better outcomes than RFA when it comes to RFS ( 39 ). Rapid advances in radiofrequency ablation equipment, improved electrodes, and the widespread use of high-resolution intraoperative ultrasound have increased the advantages of RFA.…”
Section: Discussionmentioning
confidence: 93%
“…However, few studies have elaborated on the relationship between surgical treatments and prognosis of HCC, especially in these patients with early-stage HCC (14). Currently, surgical treatment is the primary option for HCC treatment, and advances in surgery for HCC over several decades have expanded the range of surgical options (21). The results of the present study showed that surgery could offer better long-term survival than non-surgery for patients with HCC, which is consistent with several previous studies (21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surgical treatment is the primary option for HCC treatment, and advances in surgery for HCC over several decades have expanded the range of surgical options ( 21 ). The results of the present study showed that surgery could offer better long-term survival than non-surgery for patients with HCC, which is consistent with several previous studies ( 21 - 26 ). Yu et al reported that the main treatments for early HCC included liver resection, LT, and other operations such as LTD ( 24 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in minimally invasive surgery have gradually accelerated the adoption of laparoscopic liver resection (LLR), and its role in liver surgery is becoming increasingly important. Several studies have demonstrated that LLR could provide favorable short-and long-term outcomes compared with open liver resection (OLR) (8)(9)(10). However, these earlier studies included a limited number of patients who underwent laparoscopic anatomical resection (LAR), especially in the posterosuperior (PS) segments of the liver (segments 1, 7, 8, and the superior part of segment 4).…”
Section: Introductionmentioning
confidence: 99%